The use of antenatal corticosteroids for fetal maturation: clinical practice guideline by the WAPM-World Association of Perinatal Medicine and the PMF-Perinatal Medicine Foundation - Themistoklis Dagklis; Cihat Şen; Ioannis Tsakiridis; Cecilia Villalaín; Karel Allegaert; Sven Wellmann; Satoshi Kusuda; Bernat Serra; Manuel Sanchez Luna; Erasmo Huertas; Nicola Volpe; Rodrigo Ayala; et al. (Perinatal Medicine Foundation, 2022)
This practice guideline follows the mission of the World Association of Perinatal Medicine (WAPM) in collaboration with the Perinatal Medicine Foundation (PMF), bringing together groups and individuals throughout the world with the goal of improving the use of antenatal corticosteroids (ACS) for fetal maturation. In fact, this document provides further guidance for healthcare practitioners on the appropriate use of ACS with the aim to increase the timely administration and avoid unnecessary or excessive use. Therefore, it is not intended to establish a legal standard of care. This document is based on consensus among perinatal experts throughout the world and also serves as a guideline for use in clinical practice.